Effect Of Metformin In Obese Knee Osteoarthritis Patients - .S, Varshini; Karthickeyan, .K; Shanmugasundaram, P. (Journal of Neonatal Surgery, 2025)
Background: Obese knee osteoarthritis (OA) is a debilitating condition driven by mechanical stress and systemic inflammation, with limited treatments that address both symptoms and disease progression. Tramadol is commonly used for pain relief, while metformin, traditionally a diabetes medication, shows promise for its anti-inflammatory and chondroprotective effects. This study compares the efficacy of tramadol alone versus tramadol combined with metformin in managing obese knee OA. Methods: In a 12-week randomized controlled trial at St. Isabel’s Hospital, Chennai, 50 patients (BMI ≥ 30 kg/m², aged 40–60 years) with obese knee OA were assigned to two groups: Group A (tramadol) and Group B (tramadol + metformin). Outcomes included changes in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores for pain, stiffness, and function, and serum cartilage oligomeric matrix protein (COMP) levels as a biomarker of cartilage degradation. Statistical analysis used paired t-tests to assess significance. Results: Both groups showed significant improvements in WOMAC scores and COMP levels (p < 0.05). Group B (tramadol + metformin) demonstrated greater reductions in WOMAC total score (60.6 ± 9.03 to 42.6 ± 7.80 vs. 64 ± 9.37 to 51.8 ± 8.98, p = 0.00616), pain (p = 0.030), stiffness (p = 0.0001), and function (p = 0.00679) subscales, and serum COMP levels (14.04 ± 1.87 to 9.8 ± 1.49 vs. Mavericks 14.7 ± 1.82 to 11.9 ± 1.75, p ≤ 0.0001) compared to Group A. No significant BMI changes were observed in either group. Conclusion: The combination of tramadol and metformin provides superior symptomatic relief and potential chondroprotective benefits compared to tramadol alone in obese knee OA patients. These findings suggest metformin’s potential as an adjunctive therapy, warranting further investigation into its long-term disease-modifying effects